Analysis of the Indentation Size Effect in the Microhardness Measurements in B6O - Ronald Machaka; Trevor E. Derry; Iakovos Sigalas; Mathias Herrmann (Advances in Materials Science and Engineering)
The Vickers microhardness measurements of boron suboxide (B6O) ceramics prepared by uniaxial hot-pressing was investigated at indentation test loads in the range from 0.10 to 2.0 kgf. Results from the investigation indicate that the measured microhardness exhibits an indentation load dependence. Based on the results, we present a comprehensive model intercomparison study of indentation size effects (ISEs) in the microhardness measurements of hot-pressed B6O discussed using existing models, that is, the classical Meyer's law, Li and Bradt's proportional specimen resistance model (PSR), the modified proportional specimen resistance model (MPSR), and Carpinteri's multifractal scaling law (MFSL). The best correlation between literature-cited load-independent Vickers microhardness values, the measured values, and applied models was achieved in the case of the MPSR and the MFSL models.